Clinically probable RBD is an early predictor of malignant non-motor Parkinson’s disease phenotypes - Alfonso Enrique Martinez-Nunez; Hunter Hutchinson; Patricia Coutinho; Filipe Pereira Sarmento; Venkat Srikar Lavu; Qingqi Yuan; Jagan Mohan Reddy Dwarampudi; Aysegul Gunduz; Gregory M. Pontone; Michael S. Okun; Joshua K. Wong (npj Parkinson's Disease)
Abstract Non-motor symptoms (NMS) in Parkinson’s disease (PD) significantly impact quality of life, especially in later stages. REM sleep behavior disorder (RBD) affects approximately 42% of all PD patients and frequently precedes motor PD symptoms. RBD is linked to increased rates of depression and cognitive decline. This study explores how early RBD can predict the development of NMS profiles in patients, comparing those with and without early RBD. We identified a unique NMS profile associated with early RBD. These patients had a higher rate of cognitive impairment (M2 = 326.84, p < 0.001), apathy (M2 = 332.93, p < 0.001), hallucinations (M2 = 480.05, p < 0.001), depression (M2 = 480.05, p < 0.0001), anxiety (corrected p < 0.01), impulse control disorders (M2 = 77.577, p < 0.001), and autonomic dysfunction (F = 251.8, p < 0001). A survival analysis revealed an association between early RBD and faster progression to cognitive impairment. These NMS profiles may play a critical role in stratifying patients for targeted interventions.